ANALISIS PENGENDALIAN PERSEDIAAN KELAPA SAWIT DENGAN METODE ECONOMIC ORDER QUANTITY(STUDI KASUS PADA PTPN IV UNIT USAHA ADOLINA) - Ova Novi Irama; Murni Dahlena (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2021)
The aims of this study is to determine whether Economic Order Quantity method can be applied in Control of Oil Palm Inventory at PTPN IV Unit Usaha Adolina. This research was conducted by comparing between inventory controlaccording to company policy with the Economic Order Quantity method. The results of the study prove that there are total inventory cost savings of Rp. 274,320,143 in 2017, Rp. 302,087,136 in 2018 and Rp 330.090.690 in 2019 if PTPN IV Unit Usaha Adolina used the Economic Order Quantity method in controlling oil palm inventory. Ordering costs by using EOQ is more economical because the frequency of ordering supplies is reduced so as to reduce costs when ordering. However, companies cannot apply the EOQ method for several reasons, namely oil palm cannot be stored for a long time. If the oil palm is stored for too long it will increase the levels of Free Fatty Acid (ALB) which causes the quality of the oil palm to decrease. The second reason, demand for oil palm varies and is not constant in one period.